Core values as drivers of entrepreneurial performance: A study of SMEs in Uganda's central region. Issue 5 (3rd September 2019) - Kintu, Ismail; Venter, Robert
ABSTRACT: The purpose of this study was to establish whether the relationship between core values and entrepreneurial performance in Uganda's informal economy exists and whether motivation mediates the relationship. The survey was conducted in the informal economy of Uganda's central region using a structured questionnaire. The sample included three hundred eighty-six employees of Small and Medium Enterprises. Hypotheses and mediation tests were carried out by way of structural equation modeling, using Analysis of Moment Structures and Sobel's test respectively. Results from hypotheses' tests indicate significant positive relationships between core values and entrepreneurial performance. Furthermore, it was established that motivation significantly mediates the relationship between core values and entrepreneurial performance (except trust). Based on the study's results, it is recommended that Small and Medium Enterprises should seek to acquire skills on how to fully turn motivation into business advantage and how to use core values as tools for marketing the business.